Análisis del cumplimiento del artículo 106 del CONA, numeral 4 en relación a la Sentencia No. 28-15-IN/21 de la Corte Constitucional, en la Unidad de Familia, Niñez y Adolescencia del cantón Pasaje - Maldonado Gutiérrez, Miguel Ángel (2024)
The present curricular integration work aimed to analyze the impact of ruling 28-15-IN/21, which declared Article 106.4 of the Organic Code of Childhood and Adolescence unconstitutional. This document, in its Article 106, sets out the rules for the assignment of custody of children and adolescents in cases of separation or divorce of their parents. This article stated that, under equal conditions, the mother had preference for being assigned custody, disregarding the principle of the best interest of the child, parental co-responsibility, and the principle of equality. All these principles are supported by the 2008 Montecristi Constitution. The key question that leads to a hypothesis is: Is ruling 28-15-IN/21 being used as an argument for the custody of children and adolescents in the Multicompetent Judicial Unit of Cantón Pasaje? Through surveys of affected individuals, practicing lawyers, judges, and former judges, responses were obtained that led to the conclusion that even legal professionals, as it is a relatively new norm, were unaware of its publication. Consequently, custody remained within the canons of legal traditionalism. To achieve the stated objectives, the methodology was based on empirical, descriptive, deductive, analytical, hermeneutic, comparative, and statistical methods. The latter was applied through the aforementioned surveys and interviews.